Staging of pancreatic cancer based on the number of positive lymph nodes. Issue 5 (14th February 2017) - Tarantino, I; Warschkow, R; Hackert, T; Schmied, B M; Büchler, M W; Strobel, O; Ulrich, A
Abstract: Background: The International Study Group on Pancreatic Surgery has stated that at least 12 lymph nodes should be evaluated for staging of pancreatic cancer. The aim of this population-based study was to evaluate whether the number of positive lymph nodes refines staging. Methods: Patients who underwent pancreatectomy for stage I–II pancreatic cancer between 2004 and 2012 were identified from the Surveillance, Epidemiology, and End Results database. The predictive value of the number of positive lymph nodes for survival was assessed by generalized receiver operating characteristic (ROC) curve analysis and propensity score-adjusted Cox regression analysis. Results: Some 5036 patients were included, with a median of 18 (i.q.r. 15–24) lymph nodes examined. Positive lymph nodes were found in 3555 patients (70·6 per cent). The median duration of follow-up was 15 (i.q.r. 8–28) months. ROC curve analysis revealed that two positive lymph nodes best discriminated overall survival. Patients with one or two positive lymph nodes (pN1a) and those with three or more positive lymph nodes (pN1b) had an increased risk of overall mortality compared with patients who were node-negative (pN0): hazard ratio (HR) 1·47 (95 per cent c.i. 1·33 to 1·64) and HR 2·01 (1·82 to 2·22) respectively. These findings were confirmed by propensity score-adjusted Cox regression analysis. The 5-year overall survival rates were 39·8 (95 per cent c.i. 36·5 to 43·3) per cent for patients with pN0, 21·0 (18·6 to 23·6) per cent for those with pN1a and 11·4 (9·9 to 13·3) per cent for patients with pN1b disease. Conclusion: The number of positive lymph nodes in the resection specimen is a prognostic factor in patients with pancreatic cancer. Abstract : Higher number, lower survival